1970
DOI: 10.3126/kuset.v3i2.2895
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Measurement at X-Ray Centres of a few Hospitals in Kathmandu City, Nepal

Abstract: The ionizing radiation has hazardous health effects upon human exposure. Different types of cancers are reported to be arising on account of overt exposure to ionizing radiation like X-rays. This study reports occupational exposure as well as general exposure to the public and persons visiting radiology department in hospitals of Kathmandu city for diagnostic and therapeutic purposes. A portable environment radiation monitor was used to quantify the total radiation in places of work in the X-ray departments of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
9
0
3
Order By: Relevance
“…This means that photons of X-rays are penetrated through diagnostic rooms of these hospitals due to inefficiency of walls or doors of the rooms. Giri et al (2007) measured radiation dose in public area at some hospitals in Kathamandu City, it was found that the dose range was between 2.63 and 5.13 mSv/yr which exceed reference limit for public exposure. …”
Section: Resultsmentioning
confidence: 99%
“…This means that photons of X-rays are penetrated through diagnostic rooms of these hospitals due to inefficiency of walls or doors of the rooms. Giri et al (2007) measured radiation dose in public area at some hospitals in Kathamandu City, it was found that the dose range was between 2.63 and 5.13 mSv/yr which exceed reference limit for public exposure. …”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11][12][13] Bu çalışmada, röntgen teknikeri, hasta, hasta yakınları ve diğer hastane personelinin radyoloji ünitelerinde geçirdikleri süre boyunca maruz kalabilecekleri radyasyon doz değerlerinin, radyasyon güvenliğinin sağlanabilmesi için belirlenen yıllık doz limitlerinin üzerinde olup olmadığını tespit etmek amacıyla bazı devlet hastanelerinde tomografi, röntgen ve mamografi cihazlarının bulunduğu ünitelerde doz ölçümleri gerçekleştirilmiştir.…”
Section: Mesafeunclassified
“…Benzer çalışmalarda TBM-IC Mark V model iyon odası dedektörü, LB 1200 RATO/F model GM dedektörü, PALM RAD 907 model GM dedektörü, Gamma Scout GM dedektörü ve Minirad 1000+ GM radyasyon ölçüm dedektörleri kullanılmıştır. [9][10][11][12][13] Tomografi, röntgen ve mamografi cihazları-nın her biri için, iş yoğunluğunun olduğu mesai saatleri içerisinde (09.00-16.00), personelin çalı-şabileceği maksimum ışınlama şartlarında sabit bir kVp ve mAs değeri belirlenerek ölçümler gerçek-leştirilmiştir. Tomografi ünitelerinin 120 kVp ve 350 mAs**** değerinde, röntgen cihazlarının 100 kVp ve 250 mAs değerinde ve mamografi cihazlarının 30 kVp ve 200 mAs değerinde ışınlama yapılmasıyla, ölçümler üç farklı noktada alınmıştır.…”
Section: Gereç Ve Yöntemlerunclassified
See 1 more Smart Citation
“…In majority of the cases, the local or national level guidelines are less stringent compared to international guidelines, particularly driven by some cost, feasibility, and political commitment. In Nepal, emission control policies have begun after the Earth Summit 1992 with the introduction of "Vehicle emission Control in Kathmandu Valley 1993"[ 5 ] and the Constitution of Nepal 2015[ 6 ] has guaranteed people's right to live in clean and healthy environment [Article 35: 1 and 2], however, the past experiences in Nepal suggests that the implementation is of a major concern.…”
mentioning
confidence: 99%